(untitled) (London Journal of Research In Science: Natural and Formal, 2025)
This paper provides an updated analysis of cork production and its relationship to forest decline in Andalusia, southern Spain. It examines the ecological, economic, and environmental importance of cork oak forests, while evaluating the impacts of climate change, prolonged drought, wildfires, and pathogens on productivity. Based on literature reviews, historical archives, and cork extraction data from 1998 to 2023, the study identifies a sustained decrease in yields, highlighting a moderate correlation between environmental stress factors and the decline in production, indicating that socioeconomic factors modulate cork extraction and trade. Results underscore the urgent need for innovative management strategies, ecological restoration, and international cooperation to safeguard these Mediterranean ecosystems and their socio-economic benefits.